RESPON PERTUMBUHAN DAN HASIL SAWI HIJAU TERHADAP PENGGUNAAN KOMPOS SEBAGAI SUBSTITUSI PUPUK ANORGANIK - Usmadi, Usmadi; Sulistina, .; Tanzil, Ahmad Ilham; Ristiyani, Suci (Universitas Trilogi, 2023)
Increased public awareness of the importance of the availability of healthy agricultural products, including vegetables, must be supported by cultivation techniques and innovations. Cultivation of mustard greens so far still relies on the use of inorganic fertilizers as an effort to increase crop productivity. The continuous and excessive use of inorganic fertilizers not only has a negative impact on the environment but also health due to the presence of residues of hazardous materials that can be stored in plant tissues. The use of compost as a substitute for fertilizer sources in the cultivation of mustard greens is expected to reduce the negative impacts both on the environment and health. This study aimed to determine the possibility of using compost as a substitute for fertilizer in mustard green cultivation. The research is based on a Completely Randomized Design consisting of five treatments with four replications. The fertilization treatment consisted of: P1:1.4 g Urea+0.9 g SP-36+0.7 g KCl, P2:1.1 g Urea+0.7 g SP-36+0.6 g KCl+ 9 g compost, P3:0.8 g Urea+0.5 g SP-36+0.5 g KCl+18 g compost, P4:0.5 g Urea+0.3 g SP 36+0.4 g KCl +27 g compost, P5:0.2 g Urea+0.1 g SP 36+0.3 g KCl+36 g compost. The data obtained were analyzed using variance and if there were significant differences between the treatments, it was continued with the HSD test at the 5% level. The results showed that compost as a substitute for fertilizer could be applied in the cultivation of mustard greens. The addition of compost as much as 27 g/plant (3 tons/Ha) besides increasing growth is also able to increase the fresh weight of green mustard by 45,6%.